Queuing System of a Busy Restaurant Using Simulation Software - Haron, Nur Arfa Aleyssa; Kamardan, Muhamad Ghazali (Enhanced Knowledge in Sciences and Technology, 2021)
Waiting times and queuing in a long line is a common phenomenon andhas become a major problem in a busy restaurant. Time spent for the customers tobeing serve especially when waits for a long time can affect them in several of wayssuch as fatigue. This research is regarding a queuing simulation of a busy restaurantby using Arena Simulation Software. The purpose of this study is to explore more onArena Simulation Software and to analyze the queuing problem at the busy restaurant.Throughout this study, there are three variables has been analyzed such as AverageWaiting Time of Customer (Wq), Average Number of Waiting Customer (Lq) andInstantaneous Utilization. The result obtained from simulation for base modelshows the total Average Waiting Time (Wq) of a customer in queue is 55.3131minutes with the total Average Number of Customers Waiting in queue (Lq) is 10and the Instantaneous Utilization of the waiters are 72.22% and 71.33% for thecashier which is consider as well utilized and in a busy condition. Therefore, thecustomers flow in the busy restaurant system is still needed to be improved. Based onthis situation, this research also provides two (2) scenarios that help to reduce thewaiting time in a busy restaurant as well as to improve the customer’s satisfaction andincrease the restaurant efficiency.